CONTEXTUAL WORD LEARNING DURING READING IN A SECOND LANGUAGE: AN EYE-MOVEMENT STUDY. Issue 2 (21st June 2017) - Elgort, Irina; Brysbaert, Marc; Stevens, Michaël; Van Assche, Eva
Abstract: Reading affords opportunities for L2 vocabulary acquisition. Empirical research into the pace and trajectory of this acquisition has both theoretical and applied value. Charting the development of different aspects of word knowledge can verify and inform theoretical frameworks of word learning and reading comprehension. It can also inform practical decisions about using L2 readings in academic study. Monitoring readers' eye movements provides real-time data on word learning, under the conditions that closely approximate adult L2 vocabulary acquisition from reading. In this study, Dutch-speaking university students read an English expository text, while their eye movements were recorded. Of interest were patterns of change in the eye movements on the target low-frequency words that occurred multiple times in the text, and whether differences in the processing of target and control (known) words decreased overtime. Target word reading outside of the familiar text was examined in a posttest using semantically neutral sentences. The findings show that orthographic processing develops relatively quickly and reliably. However, online retrieval of meaning remains insufficient for fluent word-to-text integration even after multiple contextual encounters.